TECHNO-ECONOMIC ASSESSMENT OF TRANSFORMING SORGHUM BAGASSE INTO BIOETHANOL FUEL IN NIGERIA: 1 - PROCESS MODELLING, SIMULATION, AND COST ESTIMATION - AJAYI OLUFUNMILOLA OYENIKE; ONIFADE KOLAWOLE RASHEED; ONADEJI ABIODUN; OYEGOKE TOYESE (Journal of Engineering Studies and Research)
Apart from the environmental threats posed by fossil fuel due to emissions of greenhouse gases (majorly CO2), Nigeria's economy's continuous reliance on only one source of fuel production is unsustainable, hence, the need to consider diversification and alternative sources of energy generation and fuel production. This work aims to model and simulate the process of transforming sorghum bagasse into a fuel grade bioethanol via the use of Aspen HYSYS and MATLAB for the development and evaluation of cost implications and demand of the concerned plant studied. The study of process plant models shows that 189 g of fuel grade bioethanol will be obtainable from a kilogram of sorghum bagasse based on the condition employed in the modeling of the process. Cost analysis indicates that it would require a capital and operation cost worth of $1.92 and $ 0.83, respectively, to produce a liter of fuel grade bioethanol from sorghum bagasse.